Effects of acupuncture or similar needling therapy on pain, proprioception, balance, and self-reported function in individuals with chronic ankle instability: A systematic review and meta-analysis - Lijiang Luan; Mengda Zhu; Roger Adams; Jeremy Witchalls; Adrian Pranata; Jia Han (Elsevier, 2023)
Objective: Acupuncture or similar needling therapy has long been used to improve well-being, but its effectiveness in management of chronic ankle instability (CAI) is unclear. To investigate the efficacy of acupuncture or similar needling therapy on pain, proprioception, balance, and self-reported function in individuals with CAI. Methods: Nine databases (PubMed, Embase, Cochrane Library, Web of Science, EBSCO, PEDro, CNKI, WanFang, and CQVIP) were systematically searched from inception to April 2023. This study included randomized controlled trials involving acupuncture or similar needling therapy as an intervention for individuals with CAI. Data were extracted independently by two assessors using a standardized form. Literature quality and risk bias were assessed by using the PEDro scale. Results: Twelve trials (n = 571) were found, of which the final meta-analysis was conducted with eight. Different studies employ varying treatments, including specific needle types, techniques, and therapeutic frameworks. Compared to control without acupuncture or similar needling therapy, acupuncture or similar needling intervention resulted in improved pain (WMD 1.33, 95 % CI 0.14-2.52, I²=90 %, p = 0.03), proprioception (active joint position sense, WMD 1.71, 95 % CI 0.95-2.48, I²=0 %, p < 0.0001), balance (SMD 0.54, 95 % CI 0.03-1.04, I²=46 %, p = 0.04), and self-reported function (Cumberland Ankle Instability Tool (WMD 2.92, 95 % CI 0.94-4.90, I²=78 %, p = 0.004); American Orthopedic Foot and Ankle Society (WMD 9.36, 95 % CI 6.57-12.15, I²=0 %, p < 0.001); Foot and Ankle Ability Measure: activities of daily living (WMD 5.09, 95 % CI 1.74-8.44, I²=0 %, p = 0.003)) for individuals with CAI. Conclusions: The available evidence suggests that acupuncture or similar needling therapy may improve pain, proprioception, balance, and self-reported function in individuals with CAI, but more trials are needed to verify these findings. Furthermore, various needles and techniques using in different studies have resulted in methodologic limitations that should be addressed in the future.